Aggression and patterns of co-occurrence mental health problems in Chinese adolescents: a latent class analysis - Fajuan Rong; Mengni Wang; Chang Peng; Jie Hu; Junhan Cheng; Yan Wang; Yizhen Yu (BMC Public Health)
Abstract Background Mental health is an important aspect of adolescents’ development and well-being. Mental health problems, such as depression, anxiety, non-suicidal self-injury, suicide ideation, and suicide attempt, are recognized to be interconnected and to occur often. Research has found that aggression is connected to a variety of mental health problems. However, there’s limited knowledge about the patterns of how depression, anxiety, non-suicidal self-injury, suicide ideation, and suicide attempt co-occur, and only few studies describe their association with aggression and sex differences. Methods A cross-sectional study that involved 18,555 Chinese adolescents was performed to explore the mental health latent classes and the relationship with aggression. Results The results showed four latent classes of mental health problems: low-symptom class (70.8%), self-harm class (9.1%), emotional symptom class (13.4%), and high-symptom class (6.7%). A significant co-occurrence between depression, anxiety, non-suicidal self-injury, suicide ideation, and suicide attempt was found in the high-symptom class. Notably, higher levels of adolescent aggression were associated with comorbid moderate to high mental health problems. Similar four latent classes and associations were found across sexes. Conclusions The present study emphasized the heterogeneity of mental health problems and revealed their co-occurrence patterns. Aggression levels are associated with the latent classes in adolescents, with the most pronounced association observed in the high-symptom class. Preventing aggression could contribute to reducing the severity and co-occurring patterns of mental health problems among adolescents.